The Use of Modified Scrabble Game to Improve Students’ Vocabulary in English Class at SMAN 20 Surabaya - Khairunnisa Wijayanti; Windy Citra Negara; Linda Mayasari (PROCEEDING UMSURABAYA, 2026)
This research is a Classroom Action Research (CAR) which aims to determine the improvement of students' mastery of English vocabulary through the application of modified Scrabble game. This research was conducted in class XI-6 of SMAN 20 Surabaya in even semester of 2024/2025 academic year with 35 students. This Classroom Action Research (CAR) was conducted in two (2) cycles. Data were collected through English vocabulary mastery test. The data obtained were then analyzed descriptively, where the indicator of the success of the study was an increase in the percentage of the number of students who scored 75 after the implementation of the action using the modified scrabble game was 75%. The results of this study show that in cycle 1, there were 54.29% of learners getting a score of 75, while in cycle 2 there was an increase with a percentage of more than 75% of learners getting a score of 75 in cycle two (2) after the action using the modified scrabble game. Thus, it can be concluded that the use of modified scrabble game is known to improve the mastery of English vocabulary of students of class XI-6 SMAN 20 Surabaya.